MODIFIED TEA LEAVES RESIDUAL FOR NICOTINE ADSORPTION - AlBizreh, Y. Walid; Almostafa, rasha; ALJoubbeh, Malak (Malaysian Journal of Science, 2021)
The boiled tea leaves residual was modified with oleum of weight 1:1 to prepare an adsorbent that is capable to adsorb nicotine on its surface. The surface properties of the sample were studied by using the FT-IR spectroscopy after each treatment resulting obvious peaks that indicate the modification of the sample with oleum and the adsorption of nicotine on its surface. The concentration of nicotine in the prepared solutions was measured by the use of spectral analysis. The change of nicotineÎ„s adsorption was studied with the change of time. An increase in the adsorbed amount was noticed until the equilibrium was reached after 24hours. In addition, an increase of the adsorbed amount of nicotine with the increase of its initial concentration was observed at the room temperature. The experimental data corresponded with adsorption models of Langmuir, Freundlish and Temkin, besides, a mechanism of the adsorption of nicotine was suggested to occur with the participation of the two nitrogen atoms.